UPAYA PENGEMBANGAN TARI TUKUK TUNGGAK DI PARUMPUANG KABUPATEN LIMAPULUH KOTA - Mayrani, Wahyu; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
Abstract This study aims to express and describe the efforts of Tukuk Tunggak dance development  in the society of Parumpuang, Limapuluh Kota Regency. The type of study was qualitative research with using descriptive method. The main instrument of this study was the researcher and it was also assisted by supporting instruments such as stationery, camera and flashdisk. The types of data used were primary and secondary data. Techniques of data collection were done by using literature studies, observations, interviews and documentation. Techniques of data analysis were done by collecting data, describing data and making conclusion.The result shows  that the Tukuk Tunggak dance is an art that developed in Parumpuang, Limapuluh Kota Regency which had not been played for a long time. The development efforts are conducted by the researcher is cooperate with dance tuo, schools and society to carry out the Tukuk Tunggak dance. The activity is conducted in order to increase the dancers who are able to play and the usefulness of the Tukuk Tunggak dance is not only for the establishment of the rumah gadang but also for other events . By using the Tukuk Tunggak dance training which is held in schools, it can add the number of the dancers  in playing the Tukuk Tunggak dance which is showed at school farewell events and in the middle of society activities to e nliven Idul Fitri feast. Dance tuo hopes that the Tukuk Tunggak will develop continuously and the younger generation will recognize and know the traditional art that exist in their area and they can continue to develop the dance to the next generation. Keywords : Efforts, Development, Tukuk Tunggak Dance